CH-OST : Junge Schweizer Künstler. - Wildermuth, Armin (Sankt Gallen : Kunstverein Sankt Gallen, 1982)
Ackermann, Erika ; Brunschwiler, Leo ; Arpagaus, Elisabeth ; Calzaferri, Toni ; Eberle, Urs ; "Gam-Sun", Magnus ; Froidevaux, Pascal ; fricker, H.R. ; Gamper, Johannes ; Hanimann, Alex ; Herzog, Peter ; Heuberger, Jean-Denis ; Hohengasser, Anita ; Kälin, Felix ; Kessler, Raphael ; Kohler, Esther ; Lüchinger, Thomas ; Müller, Felix ; Schawalder, Rudolf ; Sennhauser, Monika ; Signorell, Gaudenz ; Guido ; Todesco, Luciano ; Thomann, Hans ; Zindel, Thomas ; Zünd, Marcel
CH-OST : Junge Schweizer Künstler, Kunstverein Sankt Gallen, Olma-Halle F, 26. Oktober bis 14. November 1982
boek
Keywords: Zwitserland